Metacognitive awareness and emotional resilience in children with Attention Deficit Hyperactivity Disorder - ÜNVER, HATİCE; ARMAN, AYŞE (My University, 2022)
Background: This study explored the metacognitive awareness and emotional resilience levels of children suffering from attention deficit hyperactivity disorder (ADHD) (n=60) with typically developing children (n=30). Methods: Measures included Metacognitive Awareness Inventory and Resiliency Scales for Children and Adolescents filled out by participants, the List of Adverse Life Events, Turgay DSM-IV-Based Disruptive Behavior Disorders Scale, and Revised Child Anxiety and Depression Scale—Parent Form filled out by parents. Results: Metacognitive awareness and emotional resilience were found to be low in the children with ADHD. Emotional resilience increases as metacognitive awareness increases. Metacognitive awareness decreased in the presence of heightened ADHD, anxiety, and/or depression symptoms expressed by the parents' questionnaires (p < 0.001, r = −0.438; p < 0.001, r = −0.403; and p < 0.001, r = −0.421). Conclusions: Findings identified that metacognitive skills and emotional resilience are affected in ADHD. Keywords: Attention deficit hyperactivity disorder; child; adverse life events; metacognitive awareness; emotional resilience
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; Attention deficit hyperactivity disorder; child; adverse life events; metacognitive awareness; emotional resilience; DEPRESSION SCALE; PARENT VERSION; LIFE EVENTS; ANXIETY; RUMINATION; KNOWLEDGE; BELIEFS; MODEL; ADHD; Attention deficit hyperactivity disorder; child; adverse life events; metacognitive awareness; emotional resilience